A brief review on hydrophobic modifications of glycol chitosan into amphiphilic nanoparticles for enhanced drug delivery - Chong, Wai Mun; Erazuliana Abd Kadir, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Glycol chitosan (GC) is the chitosan derivative that is capable of forming amphiphilic nanoparticles upon structure modifications at the reactive functional amine group on the polymer sugar backbone. Owing to the hydrophilic feature of GC and hydrophobic moieties that can be added to the GC structure, modifiable nanosystems were constructed to entrap poorly soluble drugs, mostly chemotherapeutic agents and several anti-inflammatory, anaesthetic, immunosuppressant, and antifungal drugs for more efficient delivery of the payload to the target site and improving the intended therapeutic effects. This review highlights the various hydrophobic molecules used in the chemical modification of GC to create amphiphilic nanoparticles for hydrophobic drug delivery, along with the summary of their physicochemical criteria and successful therapeutic enhancement achieved with the application of the drug-loaded amphiphiles. The biodegradable, GC-based nanoparticles particularly having the inner hydrophobic core and outer hydrophilic shell are an efficient system for drug entrapment, protection and targeting to improve the bioavailability and safety of the drug, in particular for cancer treatment purposes. The significant drug delivery enhancements achieved by these various hydrophobically-modified GC nanoparticles may provide the insights for their further use in nanomedicine.